2016
DOI: 10.1136/neurintsurg-2015-012206
|View full text |Cite
|
Sign up to set email alerts
|

Implications of limiting mechanical thrombectomy to patients with emergent large vessel occlusion meeting top tier evidence criteria

Abstract: Background Recent guidelines for endovascular management of emergent large vessel occlusion (ELVO) award top tier evidence to the same selective criteria in recent trials. We aimed to understand how guideline adherence would have impacted treatment numbers and outcomes in a cohort of patients from a comprehensive stroke center. Methods A retrospective observational study was conducted using consecutive emergent endovascular patients. Mechanical thrombectomy (MT) was performed with stent retrievers or large bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…We recently reported that nearly 50% of patients who underwent MT would have been denied the procedure if top-tier guidelines were strictly followed at a single center 10. Interestingly, 33% of cases treated outside these guidelines achieved functional independence at 3 months and, importantly, the procedure was safe in this cohort without excessive risk for symptomatic intracerebral hemorrhage (sICH) 10.…”
Section: Introductionmentioning
confidence: 90%
“…We recently reported that nearly 50% of patients who underwent MT would have been denied the procedure if top-tier guidelines were strictly followed at a single center 10. Interestingly, 33% of cases treated outside these guidelines achieved functional independence at 3 months and, importantly, the procedure was safe in this cohort without excessive risk for symptomatic intracerebral hemorrhage (sICH) 10.…”
Section: Introductionmentioning
confidence: 90%
“…Functional outcome was evaluated at 3 months using the modified Rankin Scale (mRS) score. Functional improvement was assessed by the shift in the distribution of 3 month mRS score,25 while functional independence was defined as a 3 month mRS score of 0–2 19. The mRS scores were obtained either from a post hospital discharge clinic follow-up or from a hospital visit.…”
Section: Methodsmentioning
confidence: 99%
“…•treatment that can be initiated within 6 hours of symptom onset (21) Selection of patients for endovascular treatment of acute ischemic stroke can be performed with the help of CT or MRI imaging.…”
Section: Discussionmentioning
confidence: 99%